RAPID ASSESSMENT ON MACRO-MOTH DIVERSITY AT GUNUNG TAMBORA NATIONAL PARK, WEST NUSA TENGGARA - Hari Sutrisno (ZOO INDONESIA, 2018)
Rapid assessment on moth fauna with focus on macro-moths was conducted at Gunung Tambora National Park from 16 to 26 April 2015. The aims of the study were to acquire information on macro-moth diversity and to access the composition of the species at this area. The result showed that a short collecting time within two sampling sites recorded only about 77.8% of estimated value in this park (242 of 311 species). Index diversity based on Fisher’s α is low (97.21). In addition, the number of families recorded from this park is also low, only 17 families, or about one third of the moth families that occur in Indo-Malayan region. Camp II site was higher than the base camp Oi Marai sites in term of the diversity index. These two sites have a few species in common as indicated by Jaccard coefficient that was low (13.8%). In general, Noctuidae (26%), Pyralidae (20%), and Geometridae (19%) dominate across all sites. Noctuidae, Geometridae, Lymantriidae were higher in Camp II than those found in Oi Marai. On the other hand,Pyralidae was higher in Oi Marai than those found in Base Camp II.Keywords: Fisher’s α, index diversity, similarity.